The Model of Based-Problem Learning, Students Problem-Solving Skills and Characteristics of Thinking Way - Dwi Oktaviana; Rahman Haryadi (Kawanua International Journal of Multicultural Studies, 2020)
This study aims to determine the differences in student's problem-solving abilities through the Problem Based Learning (PBL) model and the direct learning model, the differences in students' problem-solving abilities through the PBL model, and the direct learning model in terms of the characteristics of the way of thinking. This study used a quasi-experimental method with a two-way ANOVA design. The sample in this study was the fifth-semester students of class A and B IKIP PGRI Pontianak using the cluster random sampling technique. The used research instrument was a test of problem-solving ability in discrete mathematics courses and a questionnaire on the characteristics of the way of thinking. This study resulted in a difference between student's problem-solving abilities through the PBL model and the direct learning model. The results showed that there were no differences in students' problem-solving abilities through the PBL model and the direct learning model in terms of the characteristics of both the way of thinking, the way of thinking in Concrete Sequences (CS), Sequences Abstract (SA), Concrete Random (CR), or Abstract Random (AR).